2016
DOI: 10.1016/j.ijgo.2015.09.019
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Randomized controlled trial of elevation of the fetal head with a fetal pillow during cesarean delivery at full cervical dilatation

Abstract: Use of the Fetal Pillow in second-stage cesarean delivery significantly reduces the risk of a major extension of the uterine incision. CTRI registration number: CTRI/2015/03/005651.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 17 publications
2
39
2
Order By: Relevance
“…In the recommendations for practice, the fetal pillow receives special mention as one of the possibilities to consider when delivering a deeply impacted fetal head. 4 Seal et al 6 have completed the only RCT currently published employing the fetal pillow. They observed a decrease in their rate of uterine extension but found a major extension rate of 5% with pillow use compared to 32.5% overall in their no-pillow group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recommendations for practice, the fetal pillow receives special mention as one of the possibilities to consider when delivering a deeply impacted fetal head. 4 Seal et al 6 have completed the only RCT currently published employing the fetal pillow. They observed a decrease in their rate of uterine extension but found a major extension rate of 5% with pillow use compared to 32.5% overall in their no-pillow group.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial (RCT) was completed in 2016 in India and randomized 240 women who had a cesarean delivery at full dilatation. 6 The study suggested a benefit to patient outcomes with the use of the fetal pillow through reduced uterine angle extension (relative risk [RR] 0.37, 95% confidence interval [CI] 0.22-0.63), reduced blood loss over 1000 mL (RR 0.29, 95% CI 0.13-0.66), and reduced requirement for blood transfusion (RR 0.28, 95% CI 0.11-0.70). Data from Australia suggest that the fetal pillow may decrease blood loss intraoperatively, shorten hospital admission time, and improve fetal arterial pH when compared to the use of the "hand push" method.…”
Section: Introductionmentioning
confidence: 99%
“…We were also unable to determine the length of the first stage and the second stage of labour. Lastly, the interventions to decrease the trauma to the uterus during the delivery of the impacted foetal head have been evaluated (Jeve et al 2016; Seal et al 2016; Waterfall et al 2016). The reverse breech extraction through the hysterotomy (the ‘pull technique’) has been compared to assistance from a vaginal hand (the ‘push’ technique) in the CDs performed for a second-stage arrest in four randomised trials.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the mean length of the second stage averaged 1.9 hours. 4 Compared with no Fetal Pillow, use of the Fetal Pillow was associated with a reduction in grade 3 extension of the uterine incision (extension into the uterine artery, vagina, or bladder) (2.5% vs 23%), a reduction in blood loss > 1,000 mL (4% vs 22%), and fewer difficult plus very difficult deliveries of the fetal head as reported by the surgeon (6% vs 39%).…”
Section: Effectiveness Of the Fetal Pillowmentioning
confidence: 95%